Clinical trial designs for rare diseases 1: trial designs - Pariser, Anne (Henry Stewart Talks, 2019)
Rare disease clinical trial challenges, Rare disease clinical trial design, recent history and context, Clinical trial design overview, Selected examples of clinical trials for rare diseases